SCT2G: Model for Fast Satellite Activity Recognition in SDA - Yining Song; Zhi Li; Zhanyue Zhang (IEEE Access, 2022)
With the rapid development of space technology, the space domain environment has become increasingly complex and variable, which has created more challenges for space domain awareness. By classifying the problems faced by SDA, the overall idea of solving these problems by detecting points of variation is clarified. In this paper, a change-point detection method is constructed for space target data streams based on the T2G model, and the method’s effectiveness and performance are verified by simulating satellite data streams. This proves that the method proposed in this paper can quickly and effectively detect the change points of a civilian space target. Furthermore, we include a preliminary analysis of space target behaviour by analysing the calculated anomaly score. After verifying the method, we demonstrate its applications in several important fields (such as regular LEO satellites, LEO satellites with frequent orbit manoeuvres, and GEO satellites), which not only verifies the proposed method’s effectiveness but also yields much more space information. This can provide valuable evidence, recommendations and references for subsequent space situation analysis and space mission planning.